2001
DOI: 10.1258/1357633011936336
|View full text |Cite
|
Sign up to set email alerts
|

A cost study of teleconsultation for primary-care ophthalmology and dermatology

Abstract: Teleconsultations were performed between a health centre in a small Finnish town and a university hospital 55 km away. Telemedicine consultations were carried out with a total of 42 patients suffering from various eye and skin disorders. We evaluated the costs of the teleconsultations in the health centre and the conventional alternative of the patient travelling to the hospital. The cost of conventional consultations, which was not affected by the patient workload, was EU126 per patient for ophthalmology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 13 publications
1
18
0
1
Order By: Relevance
“…Teleophthalmology was less costly at a workload of 128 patients, suggesting an increased number of teleophthalmology consultations, coupled with decrease in cost of telecommunications and equipment will increase savings. Lamminen et al 36 estimated teleophthalmology fixed costs at €9760 and variable costs at €37.6 compared with €126 for traditional consultation. The breakeven point was ≥110 teleophthalmology consultations annually.…”
Section: Resultsmentioning
confidence: 99%
“…Teleophthalmology was less costly at a workload of 128 patients, suggesting an increased number of teleophthalmology consultations, coupled with decrease in cost of telecommunications and equipment will increase savings. Lamminen et al 36 estimated teleophthalmology fixed costs at €9760 and variable costs at €37.6 compared with €126 for traditional consultation. The breakeven point was ≥110 teleophthalmology consultations annually.…”
Section: Resultsmentioning
confidence: 99%
“…One additional study, not included in the table, used economic modeling techniques. 41 The authors reported models that indicated real-time teledermatology could be costsaving, with cost savings being largely dependent on consult volume.…”
Section: Real-timementioning
confidence: 99%
“…[6][7][8] The literature on realtime interactive teledermatology has run the gamut from teledermatology being a cost-saving strategy to one that incurs greater costs. [12][13][14][15][16][17][18] A notable deficit in the real-time interactive literature is a true cost-effectiveness analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusions vary from teledermatology being a cost-saving strategy, to a cost-neutral strategy, to one that incurs greater costs. [12][13][14][15][16][17][18] …”
Section: Real-time Interactive Teledermatologymentioning
confidence: 99%